Pengaruh GCG, Intelectual Capital, dan CAR Terhadap Kinerja Keuangan dengan ISlamic Social Reporting Indek Sebagai Variabel Intervening - Nadila, Dian Luthvita; Annisa, Arna Asna (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2021)
This study aims to determine the effect of good corporate governance, intellectual capital, and capital adequacy ratio on financial performance with the Islamic social reporting index as an intervening variable. This research uses quantitative research by using multiple linear regression analysis and path analysis as data analysis. The sampling method used purposive sampling technique by setting several criteria so that there were 11 Islamic Commercial Banks that became the research sample. This study uses secondary data in the form of panel data at Islamic Commercial Banks (BUS) for the 2015-2019 period. The data population in this study is BUS in Indonesia for the 2015-2019 period. Data processing using Eviews 9. The results of this study indicate that the frequency of board of commissioners meetings has a positive effect and the frequency of audit committee meetings has no significant negative effect, while Intellectual Capital, CAR and ISR have a significant positive effect on financial performance (ROA). The frequency of board of commissioners' meetings and CAR has a positive and insignificant effect, the frequency of audit committee meetings has a negative and insignificant effect, while Intellectual Capital has a positive and significant effect on the Islamic Social Reporting Index. The ISR index cannot mediate the effect of the frequency of board of commissioners meetings, the frequency of audit committee meetings, intellectual capital, and CAR on financial performance (ROA).